2018
DOI: 10.1016/j.vetpar.2018.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection with hydrated lime may help manage cryptosporidiosis in calves

Abstract: A B S T R A C TDiarrhea is common in young calves and is often caused by Cryptosporidium parvum infection. The aim of this study was to investigate if disinfection of calf pens with hydrated lime would reduce contamination of C. parvum oocysts and improve calf health in herds with C. parvum associated diarrhea problems. Four dairy herds with ongoing C. parvum associated calf diarrhea problems each participated in the study over six to seven months. During the study period, all pens/huts for young calves were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…Management of clinical cryptosporidiosis in pigs is supportive as there is no readily available therapeutic treatment or prophylaxis [ 3 , 31 ]. Implementing good management and biosecurity systems, to ensure sufficient sanitation and to prevent environmental contamination of oocysts should instead be the focus [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Management of clinical cryptosporidiosis in pigs is supportive as there is no readily available therapeutic treatment or prophylaxis [ 3 , 31 ]. Implementing good management and biosecurity systems, to ensure sufficient sanitation and to prevent environmental contamination of oocysts should instead be the focus [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Management of clinical cryptosporidiosis in pigs is supportive as there is no readily available therapeutic treatment or prophylaxis [ 3 , 31 ]. Implementing good management and biosecurity systems, to ensure sufficient sanitation and to prevent environmental contamination of oocysts should instead be the focus [ 31 , 32 ]. For example, solid floors with porous concrete have been associated with a higher prevalence of Cryptosporidium in pig herds compared to slatted floors [ 10 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Disinfection with recommended products can help to reduce build-up of contaminated faeces on the farm, where disinfectants containing hydrogen peroxide are the most effective [22]. A recent study has also suggested that disinfection of calf pens with hydrated lime may help to reduce onset and severity of cryptosporidiosis in calves [49]. It is advisable to house calves in similar age groups, as the younger calves are more susceptible to disease and may be vulnerable to infection if they are moved into an environment contaminated by older calves.…”
Section: Disease Prevention and Control In Livestockmentioning
confidence: 99%
“…Additionally, chromatograms from 187 samples genotyped at the National Veterinary Institute (SVA, Uppsala, Sweden) between 2013 and 2020 were inputted into the tool using both forward and reverse sequences for each sample. These samples were collected from several studies ( Pettersson et al, 2020 ; Åberg et al, 2020 ; Åberg et al, 2019 ; Björkman et al, 2018 ; Björkman et al, 2015 ; Alsmark et al, 2018 ; unpublished), outbreak investigations and sporadic cases sent for routine diagnosis. The samples were comprised of 123 cattle, 34 pigs, 20 squirrels, 4 sheep, 2 horses, 2 chital deer and 1 roe deer.…”
Section: Methodsmentioning
confidence: 99%
“…Samples tested from SVA were purified using a saturated salt/glucose flotation method and DNA was extracted as described in their respective studies ( Pettersson et al, 2020 ; Åberg et al, 2020 ; Åberg et al, 2019 ; Björkman et al, 2018 ; Björkman et al, 2015 ; Alsmark et al, 2018 ), with samples from unpublished data processed by the same method as described in Pettersson et al (2020) .…”
Section: Methodsmentioning
confidence: 99%